Nano FER molecular sieve, preparation method and application thereof, catalyst and isopropylbenzene cracking method
By using organic structure guide agent with trimethylethylammonium ion structure to prepare nano-FER molecular sieve, the problem of poor diffusion in the prior art is solved, and the efficient catalytic activity and selectivity of nano-scale molecular sieve is realized, and it is used for isopropyl benzene cleavage Efficient conversion of reactions.
Patent Information
- Application Number
- CN202310712888.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-15
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-06-15
AI Technical Summary
In the catalytic reaction, the existing FER molecular sieve cannot diffuse in time due to poor diffusion, resulting in deep side reactions and coking inactivation, shortening the catalytic life, and often requires the use of complex and expensive organic structural guides to synthesize nano-scale molecular sieve.
Using an organic structure guide agent containing trimethylethylammonium ion structure, crystallization is carried out through a mixed liquid of silicon source, aluminum source, sodium hydroxide and solvent, and calcination is used to prepare nano-FER molecular sieve, nano-flake-like with extremely small particle size Topologies and good diffusion properties.
The prepared nano FER molecular sieve has better molecular diffusion and catalytic activity, and is used to achieve high conversion and high selectivity during the isopropyl benzene cleavage reaction.
Smart Images

Figure CN119143146A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of molecular sieves, and in particular to a nano FER molecular sieve and a preparation method and application thereof, as well as a catalyst and a method for cracking cumene. Background Art
[0002] FER molecular sieve is a mesoporous molecular sieve with eight-membered ring (0.48nm×0.35nm) channels parallel to the
[010] crystal plane and ten-membered ring (0.54nm×0.45nm) channels parallel to the
[001] crystal plane interlaced to form a two-dimensional channel structure, and six-membered rings parallel to the ten-membered rings intersected with eight-membered rings to form an elliptical FER cage. Due to its unique structural system, FER molecular sieves have shown good catalytic effects in reaction systems such as isomerization, cracking, aromatization of hydrocarbons and carbonylation of dimethyl ether. At present, FER molecular sieves are mainly synthesized hydrothermally by adding organic structure-directing agents. Common organic structure-directing agents include cyclohexylamine (CN101928011B), ethylenediamine (CN104495869B), pyrrolidine, hexamethyleneimine, 1,4-cyclohexanediamine (CN102530979A), pyridine (CN102627288B), etc. There are also imidazoles (CN113979444A), N,N-diethyl-cis-2,6-dimethylpiperidine hydroxide (CN109650402B), etc.
[0003] The FER molecular sieves prepared as reported so far will limit the diffusion of reactant and product molecules in the molecular sieve to a certain extent when used, and the generated product molecules cannot diffuse out in time, resulting in deep side reactions, causing coking and deactivation, and thus shortening the catalytic life of FER. CN104495869B discloses a method for synthesizing small-grained ZSM-35 by adding seed crystals and low-temperature aging using ethylenediamine as an organic structure directing agent, and the prepared molecular sieve has poor diffusivity. CN109650402B discloses a method for preparing nano-sheet FER molecular sieves by hydrothermal synthesis using N, N-diethyl-cis-2,6-dimethylpiperidine hydroxide as an organic structure directing agent, but the structure of the organic structure directing agent is relatively complex and it is difficult to further expand its application. In summary, the generally synthesized FER molecular sieves are large in size or thicker, and a relatively complex and expensive organic structure directing agent or composition is required to synthesize nano-scale FER molecular sieves. Summary of the invention
[0004] The purpose of the present invention is to provide a nano FER molecular sieve with a new morphology and structure, a preparation method and application thereof, and a catalyst and a method for cracking isopropylbenzene.
[0005] The inventors of the present invention have discovered a nano FER molecular sieve different from the prior art through extensive and hard research. The FER molecular sieve has a nano sheet morphology with extremely small particle size, and the inventors have further discovered that the FER molecular sieve has good diffusion performance.
[0006] Based on the above findings, the first aspect of the present invention provides a nano FER molecular sieve having a nano plate-like crystal morphology with extremely small particle size; among the three dimensions of the nano plate-like crystals, the average size of at least two dimensions is not higher than 100 nm.
[0007] The second aspect of the present invention provides a method for preparing a nano FER molecular sieve, the preparation method comprising:
[0008] (1) crystallizing a raw material mixture formed by a silicon source, an aluminum source, sodium hydroxide, an organic structure directing agent and a solvent;
[0009] (2) calcining the solid product obtained in step (1);
[0010] Wherein, the organic structure directing agent is selected from quaternary ammonium salts and / or quaternary ammonium bases containing trimethylethylammonium ion structures;
[0011] In the raw material mixture, the molar ratio of silicon source, aluminum source, sodium hydroxide and organic structure directing agent is 1:a:b:c, wherein a is 0.021-0.045, b is 0.25-0.35 and c is 0.07-0.14; wherein the silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3 and the organic structure directing agent is calculated as trimethylethylammonium ion.
[0012] The third aspect of the present invention provides the use of the nano FER molecular sieve provided in the first aspect of the present invention as an adsorbent or a catalyst for conversion of organic compounds.
[0013] The fourth aspect of the present invention provides a catalyst, which comprises the nano FER molecular sieve described in the first aspect of the present invention and optionally a binder.
[0014] A fifth aspect of the present invention provides a method for cracking cumene, the method comprising: contacting cumene with the catalyst described in the fourth aspect of the present invention under cracking reaction conditions.
[0015] Compared with the prior art, the present invention has at least the following beneficial effects:
[0016] The inventors of the present invention have found that the nano FER molecular sieve of the present invention has a special morphology and good molecular diffusion during use. When it is used as a catalyst for organic compound conversion, it not only has good catalytic activity but also has high selectivity for the target product. For example, when it is used as a catalyst in the cracking reaction of cumene, cumene has a high conversion rate and the target product benzene has high selectivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 is the XRD spectrum of the molecular sieve sample in Example 1;
[0018] Figure 2 is a SEM electron microscope image of the sodium-type nano FER molecular sieve in Example 1;
[0019] Figure 3 is the XRD spectrum of the molecular sieve sample in Example 2;
[0020] Figure 4 is a SEM electron microscope image of the sodium-type nano FER molecular sieve in Example 2;
[0021] Figure 5 is the XRD spectrum of the molecular sieve sample in Example 3;
[0022] Figure 6 is the XRD spectrum of the molecular sieve sample in Example 4;
[0023] Figure 7 is the XRD spectrum of the molecular sieve sample in Example 5;
[0024] Figure 8 is the XRD spectrum of the molecular sieve sample in Example 1;
[0025] Fig. 9 This is a SEM electron microscope image of the sodium-type FER molecular sieve in Comparative Example 1;
[0026] Fig.10 is the XRD spectrum of the molecular sieve sample in Comparative Example 2;
[0027] Fig.11 This is the SEM electron microscope image of the sodium-type FER molecular sieve in Comparative Example 3. DETAILED DESCRIPTION
[0028] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0029] The first aspect of the present invention provides a nano FER molecular sieve having a nano flaky crystal morphology; among the three dimensions of the nano flaky crystals, the average size of at least two dimensions is not greater than 100 nm.
[0030] The nano FER molecular sieve of the present invention has a nano flake crystal morphology with extremely small particle size, a small grain size and good diffusion performance, so that the molecular sieve has good catalytic performance.
[0031] In the present invention, nanoplate-like crystals refer to crystals having a nanoplate-like morphology, and their size can be described using three dimensions.
[0032] According to the present invention, in some embodiments, the average size of two of the three dimensions of the nano-platelet crystals is no more than 100 nm, and the average size of the other dimension is no more than 15 nm. The molecular sieve of the above embodiment has better diffusivity, and when used as a catalyst, it has good catalytic activity.
[0033] In the present invention, it can be understood that "the average sizes of two of the dimensions are not higher than 100nm respectively, and the average size of the other dimension is not higher than 15nm" means that the average sizes of any two dimensions of the three dimensions of the nano-sheet crystals are not higher than 100nm, and the average size of the other dimension is not higher than 15nm; and the nano-sheet crystals can also be described in three dimensions by average length, average width, and average thickness. In the present invention, the average thickness of the nano-sheet crystals corresponds to a dimension with the smallest average size among the three dimensions of the nano-sheet crystals, the average length of the nano-sheet crystals corresponds to a dimension with the largest average size among the three dimensions of the nano-sheet crystals, and the width of the nano-sheet crystals corresponds to a dimension with the second largest average size among the three dimensions of the nano-sheet crystals. Since the average width of the nano-sheet crystals corresponds to a dimension with the second largest size among the three dimensions of the nano-sheet crystals, the size of the average width is not elaborated in the present invention.
[0034] According to the present invention, in some preferred embodiments, among the three dimensions of the nano-plate-like crystals, the average size of two of the dimensions is not higher than 80nm, for example, 5nm, 10nm, 30nm, 40nm, 50nm, 60nm, 65nm, 70nm or 80nm, and the range composed of any two of the above values, preferably 30-80nm; the average size of the other dimension is not higher than 13nm, for example, 1nm, 4nm, 8nm, 10nm, 11nm, 12nm or 13nm, and the range composed of any two of the above values, preferably 3-13nm. The molecular sieve using the above embodiment has better molecular diffusivity, and when it is used as a catalyst, it has good catalytic activity.
[0035] According to the present invention, in some preferred embodiments, the nano-platelet crystals with an average size of one dimension not higher than 10 nm account for at least 70% of the total crystal count. The molecular sieve using the above embodiment has better molecular diffusivity and has good catalytic activity when used as a catalyst.
[0036] In the present invention, those skilled in the art can count the number of nanoplatelet crystals with an average size of one dimension not higher than 10 nm, or the number of nanoplatelet crystals with an average size of not higher than 9 nm, or the number of nanoplatelet crystals with an average size of not higher than 8 nm as needed in actual experiments.
[0037] In the present invention, the structure of the nano FER molecular sieve is determined by an X-ray diffraction spectrum (XRD), and the X-ray diffraction spectrum (XRD) is measured by an X-ray powder diffractometer, using a Cu-Kα ray source and a nickel filter. Before the sample test, a scanning electron microscope (SEM) is used to observe the crystallization of the molecular sieve sample to confirm that the sample contains only one crystal, that is, the molecular sieve sample is a pure phase, and then an XRD test is performed on this basis to ensure that there are no interference peaks of other crystals in the diffraction peaks in the XRD spectrum; the model of the X-ray powder diffractometer is a Panalytical X PERPRO X-ray powder diffractometer, which analyzes the physical phase of the sample, and the CuKα ray source is used. Nickel filter, 2θ scanning range 2-50°, operating voltage 40KV, current 40mA, scanning rate 10° / min.
[0038] In the present invention, the model of the scanning electron microscope (SEM) of the molecular sieve is S-4800II field emission scanning electron microscope. The molecular sieve is observed under a certain magnification using the scanning electron microscope, an observation field of view is randomly selected, the mean value of the sum of a dimension (length) of the maximum size of all nano-flaky crystals in the observation field of view is calculated, the operation is repeated 10 times in total, the mean value of the sum of the mean values of 10 times is used as the average size (average length) on the dimension, the mean value of the sum of a dimension (thickness) of the minimum size of all nano-flaky crystals in the observation field of view is measured by the same method as the average size (average thickness) on the dimension, and the number of crystals with a thickness not higher than 10nm accounts for the proportion of the total number of crystals, and the operation is repeated 5 times. The average value of 5 times is used as the proportion of the number of crystals not higher than 10nm.
[0039] According to the present invention, in some embodiments, the silicon-aluminum molar ratio of the molecular sieve is 22-45, for example, 22, 24, 26.4, 28, 32, 35, 40.6, 41, 43 or 45, and a range consisting of any two of the above values. The molecular sieve using the above embodiment has better molecular diffusivity, and when used as a catalyst, it has good catalytic activity.
[0040] In the present invention, the molar ratio of silicon to aluminum in the molecular sieve is measured by an inductively coupled plasma atomic emission spectrometer (ICP) of the molecular sieve, model Varian 725-ES. Specifically, the analysis sample is dissolved with hydrofluoric acid to detect the content of the element in moles.
[0041] According to the present invention, in some embodiments, the total specific surface area of the molecular sieve is not less than 350 m 2 / g, for example 350 m 2 / g, 400m 2 / g, 426m 2 / g, 435m 2 / g, 442m 2 / g, 490m 2 / g, 512m 2 / g, 550m 2 / g, and the range of any two of the above values, preferably 400-550 m 2 The molecular sieves used in the above embodiments have better molecular diffusivity and good catalytic activity when used as catalysts.
[0042] According to the present invention, in some embodiments, the external specific surface area of the molecular sieve is not less than 120 m 2 / g, for example 120 m 2 / g, 130m 2 / g, 150m 2 / g, 160m 2 / g, 182m 2 / g, 192m 2 / g, 228m 2 / g, 230m 2 / g or 250m 2 / g, and the range of any two of the above values, preferably 120-230 m 2 The molecular sieves used in the above embodiments have better molecular diffusivity and have good catalytic activity when used as catalysts.
[0043] According to the present invention, in some embodiments, the total pore volume of the molecular sieve is not less than 0.80 cm 3 / g, for example 0.80 cm3 / g, 0.90 cm 3 / g, 1.10 cm 3 / g, 1.16 cm 3 / g, 1.35 cm 3 / g, 1.50 cm 3 / g or 2.00cm 3 / g, and the range of any two of the above values, preferably 0.80-1.50 cm 3 The molecular sieves used in the above embodiments have better molecular diffusivity and have good catalytic activity when used as catalysts.
[0044] According to the present invention, in some embodiments, the micropore volume of the molecular sieve is not less than 0.10 cm 3 / g, for example 0.10 cm 3 / g, 0.12 cm 3 / g, 0.13 cm 3 / g, 0.14 cm 3 / g, 0.15 cm 3 / g, 0.17 cm 3 / g, 0.20 cm 3 / g or 0.22 cm 3 / g, and the range of any of the above values, preferably 0.10-0.20 cm 3 The molecular sieves used in the above embodiments have better molecular diffusivity and have good catalytic activity when used as catalysts.
[0045] In the present invention, the total pore volume, micropore volume, total specific surface area and external specific surface area of the molecular sieve are measured by nitrogen physical adsorption and desorption method (BET method): the nitrogen physical adsorption and desorption isotherm of the molecular sieve is measured by a physical adsorption instrument (Micromeretic ASAP2020M physical adsorption instrument), and then calculated by the BET equation and the t-plot equation. The experimental conditions for the molecular sieve are: the measurement temperature is -196°C, and the molecular sieve is heat-treated at 550°C in air atmosphere for 6 hours before measurement, and then pre-treated at 350°C in vacuum for 4 hours.
[0046] According to the present invention, in some embodiments, the total acid amount of the molecular sieve is not less than 800 μmol / g, for example, 800 μmol / g, 900 μmol / g, 984 μmol / g, 1031 μmol / g, 1178 μmol / g, 1200 μmol / g, 1300 μmol / g, 1400 μmol / g, 1500 μmol / g, 1600 μmol / g or 1700 μmol / g, and the range composed of any two of the above values, preferably 800-1600 μmol / g. The molecular sieve using the above embodiment has better molecular diffusivity, and when it is used as a catalyst, it has good catalytic activity.
[0047] According to the present invention, in some embodiments, the amount of strong acid of the molecular sieve is not less than 300 μmol / g, for example, 300 μmol / g, 400 μmol / g, 432 μmol / g, 455 μmol / g, 500 μmol / g, 563 μmol / g, 583 μmol / g, 600 μmol / g or 650 μmol / g, and the range composed of any two of the above values, preferably 300-600 μmol / g. The molecular sieve using the aforementioned embodiment has better molecular diffusivity, and when it is used as a catalyst, it has good catalytic activity.
[0048] In the present invention, the acidity of the molecular sieve is measured by using the NH3-TPD chemical adsorption-desorption curve using the Altamira AMI-3300 instrument. Before the test, the sample is activated at 550°C for 1 hour, ammonia is adsorbed at 100°C for 20 minutes, and then desorption is detected at 100-100°C. Through Gaussian distribution peak separation, the acidity corresponding to the desorption temperature above 300°C can be considered as the acidity of a strong acid.
[0049] The second aspect of the present invention provides a method for preparing a nano FER molecular sieve, the preparation method comprising:
[0050] (1) crystallizing a raw material mixture formed by a silicon source, an aluminum source, sodium hydroxide, an organic structure directing agent and a solvent;
[0051] (2) calcining the solid product obtained in step (1);
[0052] Wherein, the structure of the organic structure directing agent contains a trimethylethylammonium ion structure;
[0053] In the raw material mixture, the molar ratio of silicon source, aluminum source, sodium hydroxide and organic structure directing agent is 1:a:b:c, wherein a is 0.021-0.045, b is 0.25-0.35 and c is 0.07-0.14; wherein the silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3 and the organic structure directing agent is calculated as trimethylethylammonium ion.
[0054] The invention provides a simple and feasible preparation method of nano FER molecular sieve. The method uses a cheap and simple organic structure directing agent containing a trimethylethylammonium ion structure to directly synthesize the FER molecular sieve of the invention. The yield of the prepared nano FER molecular sieve is high, and the yield of the molecular sieve product exceeds 85%. The prepared nano FER molecular sieve has a nano flaky crystal morphology with extremely small particle size. Among the three dimensions of the nano flaky crystal, the average size of at least two dimensions is not higher than 100 nm respectively. Finally, the prepared molecular sieve has good diffusivity and catalytic activity.
[0055] According to the present invention, in some embodiments, the organic structure directing agent is selected from a quaternary ammonium salt containing a trimethylethylammonium ion structure and / or a quaternary ammonium base containing a trimethylethylammonium ion structure. The molecular sieve prepared by the above embodiment has good diffusivity and catalytic activity.
[0056] According to the present invention, in some embodiments, the quaternary ammonium salt containing a trimethylethylammonium ion structure is selected from at least one of trimethylethylammonium chloride, trimethylethylammonium bromide and trimethylethylammonium iodide. The molecular sieve prepared by the above embodiment has good diffusivity and catalytic activity.
[0057] According to the present invention, in some embodiments, the quaternary ammonium base containing a trimethylethylammonium ion structure is selected from trimethylethylammonium hydroxide. The molecular sieve prepared by the above embodiment has good diffusivity and has good catalytic activity when used as a catalyst.
[0058] According to the present invention, in some preferred embodiments, the organic structure directing agent is a quaternary ammonium base containing a trimethylethylammonium ion structure. The molecular sieve prepared by the above preferred embodiments has good catalytic activity.
[0059] According to the present invention, in some preferred embodiments, a is 0.022-0.044. The molecular sieve prepared by the above embodiment has good diffusivity and has good catalytic activity when used as a catalyst.
[0060] According to the present invention, in some preferred embodiments, b is 0.26-0.33. The molecular sieve prepared by the above embodiment has good diffusivity and has good catalytic activity when used as a catalyst.
[0061] According to the present invention, in some preferred embodiments, c is 0.08-0.14. The molecular sieve prepared by the above embodiment has good diffusivity and has good catalytic activity when used as a catalyst.
[0062] According to the present invention, as long as the purpose of the present invention can be achieved, the amount of the solvent is not limited. In order to improve the efficiency of the crystallization reaction, in some embodiments, the molar ratio of the silicon source to the solvent is 1:10-50.
[0063] According to the present invention, as long as the purpose of the present invention can be achieved, the type of the solvent is not particularly limited, and for example, water may be included.
[0064] According to the present invention, as long as the purpose of the present invention can be achieved, the selection of the silicon source is not particularly limited. In some embodiments, the silicon source is selected from at least one of silica sol, silica gel and white carbon black.
[0065] According to the present invention, in some embodiments, the silicon source is silica sol. Those skilled in the art know that silica sol is a dispersion of nano-scale silica particles in water or solvent. The silica sol in the present invention can be obtained commercially, and it is a dispersion of nano-scale silica particles in water. The present invention does not specifically limit the content of silica in the silica sol, for example, it can be 20-50wt%. In the embodiments of the present invention, a silica sol with a silica content of 40wt% is used as an example to illustrate the advantages of the present invention, but the present invention is not limited thereto.
[0066] According to the present invention, in some embodiments, the aluminum source includes sodium aluminate. The molecular sieve prepared by the above-mentioned embodiment has good diffusivity and catalytic activity.
[0067] According to the present invention, in some preferred embodiments, the content of Al2O3 in the sodium aluminate is 38-43% by weight (for example, 38%, 39%, 40.5%, 42% or 43%, and the range of any two of the above values), and the content of Na2O is 30-33% by weight (for example, 30%, 30.6%, 32% or 33%, and the range of any two of the above values). The molecular sieve prepared by the above embodiment has good diffusivity and catalytic activity.
[0068] In the exemplary description of the embodiment of the present invention, the content of Al2O3 in sodium aluminate is 40.5% by weight, and the content of Na2O is 30.6% by weight, but the present invention is not limited thereto.
[0069] According to the present invention, the sodium aluminate sold on the market is generally industrial-grade sodium aluminate. For cost considerations, industrial-grade sodium aluminate is generally used for experiments. Industrial-grade sodium aluminate often contains hydration water. It can be understood that the content of Al2O3 in the sodium aluminate of the present invention is 38-43% by weight, the content of Na2O is 30-33% by weight, and the balance is water.
[0070] According to the present invention, as long as the purpose of the present invention can be achieved, the conditions of the crystallization treatment are not particularly limited. In order to improve the efficiency of the crystallization treatment, in some embodiments, the conditions of the crystallization treatment include: dynamic crystallization. Those skilled in the art can select the specific operation mode of dynamic crystallization as needed, such as rotating at a rotation speed of 10-60 rpm or stirring at a stirring speed of 30-300 rpm, and the present invention has no special restrictions on this.
[0071] According to the present invention, in some embodiments, the conditions of the crystallization treatment include: a crystallization temperature of 40-190°C, preferably 150-180°C.
[0072] According to the present invention, in some embodiments, the conditions of the crystallization treatment include: the crystallization time is 1.5-9.0 days, preferably 2.0-8.0 days.
[0073] According to the present invention, it can be understood that the raw material mixture in step (1) can be obtained by mixing raw materials such as a silicon source, an aluminum source, sodium hydroxide, an organic structure directing agent and a solvent, or a mixture obtained by mixing a portion of the solvent with at least one of the raw materials of the silicon source, the aluminum source, sodium hydroxide and the organic structure directing agent and then mixing the mixture with the remaining raw materials, wherein the mixing method is not particularly limited, for example, mixing and stirring at room temperature (15-30°C) for 1-6 hours.
[0074] According to the present invention, it can be understood that the solid product in step (2) is obtained from the reaction mixture obtained after the crystallization treatment in step (1). As long as the purpose of the present invention can be achieved, the solid product in step (2) can be obtained by any method in the art, for example, the product mixture obtained by the crystallization treatment in step (1) is filtered, washed with water, and dried; wherein, the drying can be carried out in an oven at 80-110°C overnight (8-12h).
[0075] According to the present invention, as long as the purpose of the present invention can be achieved, the roasting conditions in step (2) are not particularly limited. In some embodiments, in step (2), the roasting conditions include: a roasting temperature of 300-800°C, preferably 400-650°C; and a roasting time of 1-10 hours, preferably 3-6 hours.
[0076] According to the present invention, in some embodiments, the method for preparing the nano FER molecular sieve of the present invention further comprises: exchanging ammonium and performing heat treatment on the solid material obtained after calcination in step (2).
[0077] In the present invention, it can be understood that the solid material obtained after calcination in step (2) is a sodium-type nano FER molecular sieve, and the solid material obtained after calcination in step (2) can be subjected to ammonium exchange and heat treatment to prepare a hydrogen-type nano FER molecular sieve. Those skilled in the art know that the ammonium exchange and heat treatment of the sodium-type nano FER molecular sieve only convert the sodium-type molecular sieve into a hydrogen-type molecular sieve, change the acid content of the molecular sieve, and have no effect on the crystal morphology, silicon-aluminum molar ratio, specific surface area, pore volume and other characteristics of the molecular sieve.
[0078] According to the present invention, the specific operation and operation conditions of ammonium exchange are not particularly limited, and can be carried out according to conventional means in the art, for example, the solid material (sodium nano FER molecular sieve) obtained after calcination in step (2) is contacted with an aqueous solution containing ammonium ions (for example, at least one of an aqueous solution of ammonium chloride, an aqueous solution of ammonium nitrate, an aqueous solution of ammonium carbonate and an aqueous solution of ammonium sulfate). The number of ammonium exchanges can be 2-5 times, and after each exchange, the solid material is collected by centrifugation and then the next ammonium exchange is continued; the conditions of the ammonium exchange can be: 30-80°C for 1-8 hours. Specifically, the solid material (sodium nano FER molecular sieve) obtained after calcination in step (2) is subjected to ammonium ion exchange with 0.1-0.1 mol / L aqueous solution containing ammonium ions (mass ratio 1:5-20) at 30-70°C for 1-8 hours, and then centrifuged and washed, and the ammonium ion exchange is repeated 2-5 times.
[0079] According to the present invention, the specific operation and conditions of the heat treatment are not particularly limited, such as calcination after drying. Specifically, the sample obtained by ammonium exchange is dried at 80-120°C overnight and calcined in air at 500-650°C for 3-8 hours to obtain a hydrogen nano FER molecular sieve sample.
[0080] The third aspect of the present invention provides the use of the nano FER molecular sieve provided in the first aspect of the present invention as an adsorbent or a catalyst for conversion of organic compounds.
[0081] In the present invention, the nano FER molecular sieve with special morphology has good adsorption effect when used as an adsorbent, has good molecular sieve diffusivity when used as a catalyst for organic compound conversion, and has good catalytic activity when used as a catalyst.
[0082] According to the present invention, the catalyst for organic compound conversion may be exemplified by a catalyst for alkylation reaction of aromatic hydrocarbons and olefins, a catalyst for cracking reaction of cumene raw materials, a catalyst for isomerization reaction of alkanes, and the like.
[0083] The fourth aspect of the present invention provides a catalyst, which contains the nano FER molecular sieve described in the first aspect of the present invention and optionally a binder.
[0084] In the present invention, the catalyst containing the nano FER molecular sieve with the special morphology of the present invention has not only good catalytic activity but also good selectivity for the target product when used for catalytic reaction.
[0085] In the present invention, the optional binder refers to an embodiment containing a binder or an embodiment not containing a binder, that is, it can be understood that the nano FER molecular sieve described in the first aspect of the present invention can be used alone as a catalyst, and when used, it can be used in any physical form, for example, by crushing it and sieving a sample of a certain mesh size as a molecular sieve; it can also be used with an auxiliary agent such as a binder in any physical form in the art, for example, it and the binder are prepared into a strip, clover-shaped or other molded product according to a conventional method in the art and used as a catalyst.
[0086] A fifth aspect of the present invention provides a method for cracking cumene, the method comprising: contacting cumene with the catalyst described in the fourth aspect of the present invention under cracking reaction conditions.
[0087] In the present invention, the catalyst containing the nano FER molecular sieve with the special morphology of the present invention not only has high catalytic activity in the cumene cracking reaction, can achieve high conversion rate of cumene, but also has high selectivity for target products, that is, high selectivity for benzene.
[0088] According to the present invention, as long as the purpose of the present invention can be achieved, the cleavage reaction conditions are not particularly limited. In some embodiments, the cleavage reaction conditions include: a reaction temperature of 280-330°C.
[0089] According to the present invention, in some embodiments, the cracking reaction conditions include: the reaction pressure is normal pressure.
[0090] According to the present invention, in some embodiments, the cracking reaction conditions include: a weight space velocity of cumene of 3-6h -1 .
[0091] The present invention will be described in detail below by way of examples. In the following examples and comparative examples:
[0092] The yield of molecular sieve refers to the percentage of the mass of the sample after calcination to the sum of the mass of SiO2 and Al2O3 contained in the raw materials.
[0093] Cumene cracking reaction: crush the hydrogen type (nano FER) molecular sieve and sieve out a sample with a particle size of 20-40 mesh as a catalyst for cumene cracking reaction. Specifically, put the catalyst into a fixed bed reactor to carry out cumene cracking reaction. The reaction conditions include: reaction temperature of 280-330°C, reaction pressure of normal pressure, cumene weight space velocity of 3-6h -1 .
[0094] The cumene cracking reaction uses cumene as a raw material and cracks it into products such as propylene and benzene under the action of a catalyst.
[0095] Conversion rate of cumene % = (molar amount of feed cumene - molar amount of cumene in product) / (molar amount of feed cumene) × 100%.
[0096] Benzene selectivity % = (molar amount of benzene in the product) / (total molar amount of aromatics in the product) × 100%;
[0097] The aromatic hydrocarbons in the product do not include the raw material cumene.
[0098] Example 1
[0099] 17.24 g of deionized water, 0.612 g of sodium aluminate (containing 40.5 wt % of Al2O3, 30.6 wt % of Na2O, and the balance being H2O), 0.780 g of sodium hydroxide, 3.58 g of trimethylethylammonium hydroxide aqueous solution (containing 25.00 wt % of trimethylethylammonium hydroxide) and 12.78 g of silica sol (containing 40.0 wt % of SiO2) were stirred at room temperature for 4 hours to obtain a mixture. The final mixture ratio (molar ratio) was:
[0100] SiO2 / Al2O3=35;
[0101] NaOH / SiO2=0.30;
[0102] Trimethylethylammonium hydroxide / SiO2=0.10;
[0103] H2O / SiO2=18;
[0104] The mixture was placed in a stainless steel reactor, heated and crystallized at 170°C and 20 rpm for 3 days; after the crystallization, it was filtered and washed, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample.
[0105] The XRD spectrum of the molecular sieve sample is as follows Figure 1 As shown, through Figure 1 The molecular sieve sample can be obtained as a molecular sieve with FER structure (i.e., sodium-type FER molecular sieve);
[0106] The yield of sodium FER molecular sieve is 88wt%;
[0107] The SiO2 / Al2O3 molar ratio of the sodium FER molecular sieve was measured by inductively coupled plasma atomic emission spectroscopy (ICP) to be 34.8;
[0108] The SEM electron microscope image of the sodium FER molecular sieve is as follows Figure 2 As shown, through Figure 2 It can be obtained that the sodium FER molecular sieve has a nano-platelet crystal morphology with extremely small particle size, the average length of the nano-platelet crystal is 80nm, the average thickness of the nano-platelet crystal is 12nm, and the nano-platelet crystals with a thickness of no more than 10nm account for 70% of the total crystal count;
[0109] The total specific surface area of sodium FER molecular sieve is 489 m 2 / g, the external specific surface area measured by BET method is 177 m 2 / g; total pore volume 1.10 cm 3 / g, micropore volume is 0.13 cm 3 / gram.
[0110] The sodium FER molecular sieve was subjected to ammonium ion exchange with 0.2 mol / L NH4NO3 aqueous solution (mass ratio 1:20) at 65°C for 2 hours, followed by centrifugal washing. The ammonium ion exchange was repeated twice, and the obtained sample was dried at 100°C overnight, and then calcined in air at 550°C for 4 hours to obtain a hydrogen FER molecular sieve. The total acid content of the hydrogen FER molecular sieve was measured by NH3-TPD to be 1178 μmol / g, and the strong acid content was 457 μmol / g.
[0111] The hydrogen-type FER molecular sieve was used to carry out the cumene cracking reaction. The reaction conditions were: reaction temperature of 300°C, reaction pressure of normal pressure, and cumene weight space velocity of 6h -1 , the reaction time was 60h, the final conversion rate of isopropylbenzene was 80.6%, and the selectivity of benzene was 95.7%.
[0112] Example 2
[0113] Take 8.11 g of deionized water, 0.373 g of sodium aluminate (containing 40.5 wt% of Al2O3, 30.6 wt% of Na2O, and the balance is H2O), 0.612 g of sodium hydroxide, 2.00 g of trimethylethylammonium hydroxide aqueous solution (containing 25.00 wt% of trimethylethylammonium hydroxide) and 8.91 g of silica sol (containing 40.0 wt% of SiO2), stir at room temperature for 4 hours to obtain a mixture, and the final mixture ratio (molar ratio) is:
[0114] SiO2 / Al2O3=40;
[0115] NaOH / SiO2=0.32;
[0116] Trimethylethylammonium hydroxide / SiO2=0.08;
[0117] H2O / SiO2=14;
[0118] The mixture was placed in a stainless steel reactor, heated and crystallized at 165°C and 20 rpm for 5 days; after the crystallization, it was filtered and washed, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample.
[0119] The XRD spectrum of the molecular sieve sample is as follows Figure 3 As shown, through Figure 3 The molecular sieve sample can be obtained as a molecular sieve with FER structure (i.e., sodium-type FER molecular sieve);
[0120] The yield of sodium FER molecular sieve is 90wt%;
[0121] The SiO2 / Al2O3 molar ratio of the sodium FER molecular sieve was measured by inductively coupled plasma atomic emission spectroscopy (ICP) to be 40.6;
[0122] The SEM electron microscope image of the sodium FER molecular sieve is as follows Figure 4 As shown, through Figure 4 It can be obtained that the sodium FER molecular sieve has a nano-platelet crystal morphology with extremely small particle size, the average length of the nano-platelet crystal is 70nm, the average thickness of the nano-platelet crystal is 11nm, and the nano-platelet crystals with a thickness of no more than 9nm account for 70% of the total crystal count;
[0123] The total specific surface area of sodium FER molecular sieve is 512 m 2 / g, the external specific surface area measured by BET method is 182 m 2 / g; total pore volume 1.16 cm 3 / g, micropore volume is 0.13 cm 3 / gram.
[0124] The sodium FER molecular sieve was subjected to ammonium ion exchange with 0.2 mol / L NH4NO3 aqueous solution (mass ratio 1:20) at 65°C for 2 hours, followed by centrifugal washing. The ammonium ion exchange was repeated twice, and the obtained sample was dried at 100°C overnight, and then calcined in air at 550°C for 4 hours to obtain a hydrogen FER molecular sieve. The total acid content of the hydrogen FER molecular sieve was measured by NH3-TPD to be 984 μmol / g, and the strong acid content was 404 μmol / g.
[0125] The hydrogen-type FER molecular sieve was used to carry out the cumene cracking reaction. The reaction conditions were: reaction temperature of 310°C, reaction pressure of normal pressure, and cumene weight space velocity of 3h -1 , the reaction time was 60h, the final conversion rate of isopropylbenzene was 83.6%, and the selectivity of benzene was 95.2%.
[0126] Example 3
[0127] According to the method of Example 1, the raw material ratio is adjusted, and the ratio (molar ratio) of the final mixture is:
[0128] SiO2 / Al2O3=30;
[0129] NaOH / SiO2=0.30;
[0130] Trimethylethylammonium hydroxide / SiO2=0.12;
[0131] H2O / SiO2=22;
[0132] The mixture was placed in a stainless steel reactor, heated and crystallized at 160°C and 30 rpm for 6 days; after the crystallization, it was filtered and washed, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample.
[0133] The XRD spectrum of the molecular sieve sample is as follows Figure 5 As shown, through Figure 5 The molecular sieve sample can be obtained as a molecular sieve with FER structure (i.e., sodium-type FER molecular sieve);
[0134] The yield of sodium FER molecular sieve is 88wt%;
[0135] The SiO2 / Al2O3 molar ratio of the sodium FER molecular sieve was measured by inductively coupled plasma atomic emission spectroscopy (ICP) to be 30.4;
[0136] SEM electron microscope image of sodium FER molecular sieve and Figure 2Similarly, the sodium FER molecular sieve has a nano-platelet crystal morphology with extremely small particle size, the average length of the nano-platelet crystal is 75nm, the average thickness of the nano-platelet crystal is 12nm, and the nano-platelet crystals with a thickness of no more than 10nm account for 75% of the total crystal count;
[0137] The total specific surface area of sodium nano-FER molecular sieve is 506 m 2 / g, the external specific surface area measured by BET method is 228 m 2 / g; total pore volume 1.35 cm 3 / g, micropore volume is 0.14 cm 3 / gram.
[0138] The sodium FER molecular sieve was subjected to ammonium ion exchange with 0.2 mol / L NH4NO3 aqueous solution (mass ratio 1:20) at 65°C for 2 hours, followed by centrifugal washing. The ammonium ion exchange was repeated twice, and the obtained sample was dried at 100°C overnight, and then calcined in air at 550°C for 4 hours to obtain a hydrogen FER molecular sieve. The total acid content of the hydrogen FER molecular sieve was measured by NH3-TPD to be 1291 μmol / g, and the strong acid content was 476 μmol / g.
[0139] The hydrogen-type FER molecular sieve was used to carry out the cumene cracking reaction. The reaction conditions were: reaction temperature of 320°C, reaction pressure of normal pressure, and cumene weight space velocity of 5h -1 , the reaction time was 60h, the final conversion rate of isopropylbenzene was 82.1%, and the selectivity of benzene was 95.4%.
[0140] Example 4
[0141] The method of Example 1 is followed, except that trimethylethylammonium chloride is used as the organic structure directing agent, and the raw material ratio is adjusted. The final ratio (molar ratio) of the mixture is:
[0142] SiO2 / Al2O3=26;
[0143] NaOH / SiO2=0.28;
[0144] Trimethylethylammonium chloride / SiO2=0.14;
[0145] H2O / SiO2=24;
[0146] The mixture was placed in a stainless steel reactor, heated and crystallized at 155°C and 30 rpm for 7 days; after the crystallization, it was filtered and washed, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample.
[0147] The XRD spectrum of the molecular sieve sample is as follows Figure 6 As shown, through Figure 6 The molecular sieve sample can be obtained as a molecular sieve with FER structure (i.e., sodium-type FER molecular sieve);
[0148] The yield of sodium FER molecular sieve is 87wt%;
[0149] The SiO2 / Al2O3 molar ratio of the sodium FER molecular sieve was measured by inductively coupled plasma atomic emission spectroscopy (ICP) to be 26.4;
[0150] SEM electron microscope image of sodium FER molecular sieve and Figure 2 Similarly, the sodium FER molecular sieve has a nano-platelet crystal morphology with extremely small particle size, the average length of the nano-platelet crystal is 70nm, the average thickness of the nano-platelet crystal is 10nm, and the nano-platelet crystals with a thickness of no more than 10nm account for 80% of the total crystal count;
[0151] The total specific surface area of sodium FER molecular sieve is 442 m 2 / g, the external specific surface area measured by BET method is 196 m 2 / g; total pore volume 1.02 cm 3 / g, micropore volume is 0.13 cm 3 / gram.
[0152] The sodium FER molecular sieve was subjected to ammonium ion exchange with 0.2 mol / L NH4NO3 aqueous solution (mass ratio 1:20) at 65°C for 2 hours, followed by centrifugal washing. The ammonium ion exchange was repeated twice, and the obtained sample was dried at 100°C overnight, and then calcined in air at 550°C for 4 hours to obtain a hydrogen FER molecular sieve. The total acid content of the hydrogen FER molecular sieve was measured by NH3-TPD to be 1429 μmol / g, and the strong acid content was 563 μmol / g.
[0153] The hydrogen-type FER molecular sieve was used to carry out the cumene cracking reaction. The reaction conditions were: reaction temperature of 290°C, reaction pressure of normal pressure, and cumene weight space velocity of 3h -1 , the reaction time was 60h, the final conversion rate of isopropylbenzene was 79.6%, and the selectivity of benzene was 94.9%.
[0154] Example 5
[0155] The method of Example 1 is followed, except that trimethylethylammonium bromide is used as the organic structure directing agent, and the raw material ratio is adjusted. The final ratio (molar ratio) of the mixture is:
[0156] SiO2 / Al2O3=32;
[0157] NaOH / SiO2=0.26;
[0158] Trimethylethylammonium bromide / SiO2=0.10;
[0159] H2O / SiO2=28;
[0160] The mixture was placed in a stainless steel reactor, heated and crystallized at 180°C and 10 rpm for 2 days; after the crystallization, it was filtered and washed, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample.
[0161] The XRD spectrum of the molecular sieve sample is as follows Figure 7 As shown, through Figure 7 The molecular sieve sample can be obtained as a molecular sieve with FER structure (i.e., sodium-type FER molecular sieve);
[0162] The yield of sodium FER molecular sieve is 89wt%;
[0163] The SiO2 / Al2O3 molar ratio of the sodium FER molecular sieve was measured by inductively coupled plasma atomic emission spectroscopy (ICP) to be 31.7;
[0164] SEM electron microscope image of sodium FER molecular sieve and Figure 2 Similarly, the sodium FER molecular sieve has a nano-platelet crystal morphology with extremely small particle size, the average length of the nano-platelet crystal is 65nm, the average thickness of the nano-platelet crystal is 12nm, and the nano-platelet crystals with a thickness of no more than 10nm account for 75% of the total crystal count;
[0165] The total specific surface area of sodium FER molecular sieve is 508 m 2 / g, the external specific surface area measured by BET method is 191 m 2 / g; total pore volume 0.98 cm 3 / g, micropore volume is 0.12 cm 3 / gram.
[0166] The sodium FER molecular sieve was subjected to ammonium ion exchange with 0.2 mol / L NH4NO3 aqueous solution (mass ratio 1:20) at 65°C for 2 hours, followed by centrifugal washing. The ammonium ion exchange was repeated twice, and the obtained sample was dried at 100°C overnight, and then calcined in air at 550°C for 4 hours to obtain a hydrogen FER molecular sieve. The total acid content of the hydrogen FER molecular sieve was measured by NH3-TPD to be 1197 μmol / g, and the strong acid content was 455 μmol / g.
[0167] The hydrogen-type FER molecular sieve was used to carry out the cumene cracking reaction. The reaction conditions were: reaction temperature of 280°C, reaction pressure of normal pressure, and cumene weight space velocity of 5h -1 , the reaction time was 60h, the final conversion rate of isopropylbenzene was 78.4%, and the selectivity of benzene was 95.6%.
[0168] Example 6
[0169] According to the method of Example 1, the raw material ratio is adjusted, and the ratio (molar ratio) of the final mixture is:
[0170] SiO2 / Al2O3=28;
[0171] NaOH / SiO2=0.26;
[0172] Trimethylethylammonium hydroxide / SiO2=0.08;
[0173] H2O / SiO2=36;
[0174] The mixture was placed in a stainless steel reactor, heated and crystallized at 170°C and 20 rpm for 3.5 days; after the crystallization, it was filtered and washed, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample.
[0175] The XRD spectrum of the molecular sieve sample is as follows Figure 1 Similarly, the molecular sieve sample obtained is a molecular sieve with a FER structure (i.e., a sodium-type FER molecular sieve);
[0176] The yield of sodium FER molecular sieve is 91wt%;
[0177] The SiO2 / Al2O3 molar ratio of the sodium FER molecular sieve was measured by inductively coupled plasma atomic emission spectroscopy (ICP) to be 28.0;
[0178] SEM electron microscope image of sodium FER molecular sieve and Figure 2 Similarly, the sodium FER molecular sieve has a nano-platelet crystal morphology with extremely small particle size, the average length of the nano-platelet crystal is 70nm, the average thickness of the nano-platelet crystal is 10nm, and the nano-platelet crystals with a thickness of no more than 10nm account for 85% of the total crystal count;
[0179] The total specific surface area of sodium FER molecular sieve is 435 m 2 / g, the external specific surface area measured by BET method is 164 m 2 / g; total pore volume 1.06 cm 3 / g, micropore volume is 0.14 cm 3 / gram.
[0180] The sodium FER molecular sieve was subjected to ammonium ion exchange with 0.2 mol / L NH4NO3 aqueous solution (mass ratio 1:20) at 65°C for 2 hours, followed by centrifugal washing. The ammonium ion exchange was repeated twice, and the obtained sample was dried at 100°C overnight, and then calcined in air at 550°C for 4 hours to obtain a hydrogen FER molecular sieve. The total acid content of the hydrogen FER molecular sieve was measured by NH3-TPD to be 1302 μmol / g, and the strong acid content was 432 μmol / g.
[0181] The hydrogen-type FER molecular sieve was used to carry out the cumene cracking reaction. The reaction conditions were: reaction temperature of 320°C, reaction pressure of normal pressure, and cumene weight space velocity of 3h -1 , the reaction time was 60h, the final conversion rate of isopropylbenzene was 83.1%, and the selectivity of benzene was 96.1%.
[0182] Example 7
[0183] According to the method of Example 1, the raw material ratio is adjusted, and the ratio (molar ratio) of the final mixture is:
[0184] SiO2 / Al2O3=38;
[0185] NaOH / SiO2=0.30;
[0186] Trimethylethylammonium hydroxide / SiO2=0.12;
[0187] H2O / SiO2=32;
[0188] The mixture was placed in a stainless steel reactor, heated and crystallized at 175°C and 40 rpm for 2.5 days; after the crystallization, it was filtered and washed, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample.
[0189] XRD spectra of molecular sieve samples and Figure 1 Similarly, the molecular sieve sample can be obtained as a molecular sieve with a FER structure (i.e., a sodium-type FER molecular sieve);
[0190] The yield of sodium FER molecular sieve is 91wt%;
[0191] The SiO2 / Al2O3 molar ratio of the sodium FER molecular sieve was measured by inductively coupled plasma atomic emission spectroscopy (ICP) to be 37.8;
[0192] SEM electron microscope image of sodium FER molecular sieve and Figure 2Similarly, the sodium FER molecular sieve has a nano-platelet crystal morphology with extremely small particle size, the average length of the nano-platelet crystal is 60nm, the average thickness of the nano-platelet crystal is 12nm, and the nano-platelet crystals with a thickness of no more than 8nm account for 75% of the total crystal count;
[0193] The total specific surface area of sodium FER molecular sieve is 426 m 2 / g, the external specific surface area measured by BET method is 159 m 2 / g; total pore volume 0.91 cm 3 / g, micropore volume is 0.14 cm 3 / gram.
[0194] The sodium FER molecular sieve was subjected to ammonium ion exchange with 0.2 mol / L NH4NO3 aqueous solution (mass ratio 1:20) at 65°C for 2 hours, followed by centrifugal washing. The ammonium ion exchange was repeated twice, and the obtained sample was dried at 100°C overnight, and then calcined in air at 550°C for 4 hours to obtain a hydrogen FER molecular sieve. The total acid content of the hydrogen FER molecular sieve was measured by NH3-TPD to be 1031 μmol / g, and the strong acid content was 446 μmol / g.
[0195] The hydrogen-type FER molecular sieve was used to carry out the cumene cracking reaction. The reaction conditions were: reaction temperature of 330°C, reaction pressure of normal pressure, and cumene weight space velocity of 5h -1 , the reaction time was 60h, the final conversion rate of isopropylbenzene was 83.5%, and the selectivity of benzene was 95.7%.
[0196] Example 8
[0197] According to the method of Example 1, the raw material ratio is adjusted, and the ratio (molar ratio) of the final mixture is:
[0198] SiO2 / Al2O3=24;
[0199] NaOH / SiO2=0.32;
[0200] Trimethylethylammonium hydroxide / SiO2=0.10;
[0201] H2O / SiO2=40;
[0202] The mixture was placed in a stainless steel reactor, heated and crystallized at 165°C and 10 rpm for 4 days; after the crystallization, it was filtered and washed, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample.
[0203] XRD spectra of molecular sieve samples and Figure 1 Similarly, the molecular sieve sample can be obtained as a molecular sieve with a FER structure (i.e., a sodium-type FER molecular sieve);
[0204] The yield of sodium FER molecular sieve is 86wt%;
[0205] The SiO2 / Al2O3 molar ratio of the sodium FER molecular sieve was measured by inductively coupled plasma atomic emission spectroscopy (ICP) to be 24.1;
[0206] SEM electron microscope image of sodium FER molecular sieve and Figure 2 Similarly, the sodium FER molecular sieve has a nano-platelet crystal morphology with extremely small particle size, the average length of the nano-platelet crystal is 65nm, the average thickness of the nano-platelet crystal is 10nm, and the nano-platelet crystals with a thickness of no more than 9nm account for 70% of the total crystal count;
[0207] The total specific surface area of sodium FER molecular sieve is 481 m 2 / g, the external specific surface area measured by BET method is 172 m 2 / g; total pore volume 0.95 cm 3 / g, micropore volume is 0.13 cm 3 / gram.
[0208] The sodium FER molecular sieve was subjected to ammonium ion exchange with 0.2 mol / L NH4NO3 aqueous solution (mass ratio 1:20) at 65°C for 2 hours, followed by centrifugal washing. The ammonium ion exchange was repeated twice, and the obtained sample was dried at 100°C overnight, and then calcined in air at 550°C for 4 hours to obtain a hydrogen FER molecular sieve. The total acid content of the hydrogen FER molecular sieve was measured by NH3-TPD to be 1503 μmol / g, and the strong acid content was 583 μmol / g.
[0209] The hydrogen-type FER molecular sieve was used to carry out the cumene cracking reaction. The reaction conditions were: reaction temperature of 320°C, reaction pressure of normal pressure, and cumene weight space velocity of 5h -1 , the reaction time was 60h, the final conversion rate of isopropylbenzene was 82.1%, and the selectivity of benzene was 95.4%.
[0210] Example 9
[0211] The method of Example 1 is followed, except that the sodium aluminate used contains 50.6 wt % Al2O3, 40.1 wt % Na2O, and the balance is water, and the amount of each raw material is controlled so that the ratio (molar ratio) of the mixture is the same as that of Example 1:
[0212] XRD spectra of molecular sieve samples and Figure 1 Similar, through Figure 1 The molecular sieve sample can be obtained as a molecular sieve with FER structure;
[0213] The yield of sodium FER molecular sieve is 81wt%;
[0214] The SiO2 / Al2O3 molar ratio of the sodium FER molecular sieve was measured to be 35.8 by inductively coupled plasma atomic emission spectroscopy (ICP);
[0215] The SEM electron microscope image of the sodium FER molecular sieve is as follows Figure 8 As shown, the nanosheet crystals have a long strip-shaped morphology, and the average length of the crystals is 95nm; the average thickness of the flaky crystals is 15nm, and the nanosheet crystals with a thickness of no more than 10nm account for 70% of the total number of crystals.
[0216] The total specific surface area of sodium nano-FER molecular sieve is 441 m 2 / g, the external specific surface area measured by BET method is 103 m 2 / g; total pore volume 0.36 cm 3 / g, micropore volume is 0.15 cm 3 / gram.
[0217] The sodium FER molecular sieve was used to carry out ammonium exchange, drying and calcination according to the method of Example 1 to obtain a hydrogen FER molecular sieve. The total acid content of the hydrogen FER molecular sieve was 1046 μmol / g and the strong acid content was 376 μmol / g as measured by NH3-TPD.
[0218] The hydrogen-type FER molecular sieve was used to carry out the cumene cracking reaction. The reaction conditions were the same as those in Example 1. The final cumene conversion rate was 75.1% and the benzene selectivity was 93.6%.
[0219] Example 10
[0220] According to the method of Example 1, the raw material ratio is adjusted, and the ratio (molar ratio) of the final mixture is:
[0221] SiO2 / Al2O3=50;
[0222] NaOH / SiO2=0.35;
[0223] Trimethylethylammonium hydroxide / SiO2=0.06;
[0224] H2O / SiO2=24.
[0225] XRD spectra of molecular sieve samples and Figure 1 Similar, through Figure 1 The molecular sieve sample can be obtained as a molecular sieve with FER structure (i.e., sodium-type FER molecular sieve);
[0226] The yield of sodium FER molecular sieve is 82wt%;
[0227] The SiO2 / Al2O3 molar ratio of the sodium FER molecular sieve was measured to be 51.6 by inductively coupled plasma atomic emission spectroscopy (ICP);
[0228] SEM electron microscope image of sodium FER molecular sieve and Figure 8 Similarly, the nanosheet crystals have a long strip-shaped morphology, with an average length of 95 nm. The average thickness of the nanosheet crystals is 14 nm, and the nanosheet crystals with a thickness of no more than 10 nm account for 70% of the total crystal count.
[0229] The total specific surface area of sodium FER molecular sieve is 451 m 2 / g, the external specific surface area measured by BET method is 48 m 2 / g; total pore volume 0.44 cm 3 / g, micropore volume is 0.13 cm 3 / gram.
[0230] The sodium FER molecular sieve was used to carry out ammonium exchange, drying and calcination according to the method of Example 1 to obtain a hydrogen FER molecular sieve. The total acid content of the hydrogen FER molecular sieve was 764 μmol / g and the strong acid content was 278 μmol / g as measured by NH3-TPD.
[0231] The hydrogen-type FER molecular sieve was used to carry out the cumene cracking reaction. The reaction conditions were the same as those in Example 1. The final cumene conversion rate was 74.5% and the benzene selectivity was 92.7%.
[0232] Comparative Example 1
[0233] The method of Example 1 is followed, except that the amount of each raw material added is controlled so that the ratio (molar ratio) of the mixture is:
[0234] SiO2 / Al2O3=15;
[0235] NaOH / SiO2=0.30;
[0236] Trimethylethylammonium hydroxide / SiO2=0.10;
[0237] H2O / SiO2=18.
[0238] The XRD spectrum of the molecular sieve sample is as follows Fig. 9 As shown, through Fig. 9 The molecular sieve sample obtained is a molecular sieve with a coexistence of a MOR structure and a FER structure, but not a FER molecular sieve.
[0239] The above molecular sieve sample was used to carry out ammonium exchange according to the method of Example 1, and then dried and calcined to obtain a hydrogen-type molecular sieve.
[0240] The cumene cracking reaction was carried out using hydrogen molecular sieves, and the reaction conditions were the same as those in Example 1. The final cumene conversion rate was 42.8% and the benzene selectivity was 82.3%.
[0241] Comparative Example 2
[0242] The method of Example 1 is followed, except that the amount of each raw material added is controlled so that the ratio (molar ratio) of the mixture is:
[0243] SiO2 / Al2O3=35;
[0244] NaOH / SiO2=0.30;
[0245] Trimethylethylammonium hydroxide / SiO2=0.05;
[0246] H2O / SiO2=18.
[0247] The XRD spectrum of the molecular sieve sample is as follows Fig.10 As shown, through Fig.10 It can be obtained that the molecular sieve sample is not crystallized and has an amorphous structure, and is not a FER molecular sieve.
[0248] Comparative Example 3
[0249] According to the method of Example 1, the difference is that cyclohexylamine is used as the organic structure directing agent: the amount of each raw material added is controlled so that the ratio (molar ratio) of the mixture is:
[0250] SiO2 / Al2O3=35;
[0251] NaOH / SiO2=0.30;
[0252] Cyclohexylamine / SiO2=0.10;
[0253] H2O / SiO2=18;
[0254] The mixture was placed in a stainless steel reactor, heated and crystallized at 170°C and 20 rpm for 3 days; after the crystallization, it was filtered and washed, dried in an oven at 100°C overnight, and calcined in air at 550°C for 6 hours to obtain a molecular sieve sample.
[0255] XRD spectra of molecular sieve samples and Figure 1 Similar, through Figure 1 The molecular sieve sample can be obtained as a molecular sieve with FER structure;
[0256] The yield of sodium FER molecular sieve is 74wt%;
[0257] The SiO2 / Al2O3 molar ratio of the sodium FER molecular sieve was measured to be 34.1 by inductively coupled plasma atomic emission spectroscopy (ICP);
[0258] The SEM electron microscope image of the sodium FER molecular sieve is as follows Fig.11 As shown, it has a plate-like crystal morphology, the average length of the plate-like crystals is 3000nm; the average thickness of the plate-like crystals is 50nm, and the nanoplate-like crystals with a thickness not higher than 10nm account for 0% of the total crystal count;
[0259] The total specific surface area of sodium FER molecular sieve is 413 m 2 / g, the external specific surface area measured by BET method is 19 m 2 / g; total pore volume 0.20 cm 3 / g, micropore volume is 0.14 cm 3 / gram.
[0260] The sodium FER molecular sieve was used to carry out ammonium exchange, drying and calcination according to the method of Example 1 to obtain a hydrogen FER molecular sieve. The total acid content of the hydrogen FER molecular sieve was 1079 μmol / g and the strong acid content was 310 μmol / g as measured by NH3-TPD.
[0261] The hydrogen-type FER molecular sieve was used to carry out the cumene cracking reaction. The reaction conditions were the same as those in Example 1. The final cumene conversion rate was 48.6% and the benzene selectivity was 90.6%.
[0262] It can be seen from the results of the examples and comparative examples that the nano FER molecular sieve with a special morphology of the present invention not only has good diffusivity and catalytic activity, but also has good selectivity for the target product. When used as a catalyst for cumene cracking reaction, the conversion rate of cumene is high and the selectivity of benzene is good.
[0263] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A nano FER molecular sieve, characterized in that: The molecular sieve has a nano-platelet crystal morphology; among the three dimensions of the nano-platelet crystal, the average size of at least two dimensions is not higher than 100 nm respectively.
2. The molecular sieve according to claim 1, wherein Among the three dimensions of the nanoplate-like crystals, the average size of two of the dimensions is no more than 100 nm, and the average size of the other dimension is no more than 15 nm; Preferably, among the three dimensions of the nano-plate-like crystals, the average size of two of the dimensions is not higher than 80 nm, preferably 30-80 nm; the average size of the other dimension is not higher than 13 nm, preferably 3-13 nm; and / or The nanoplate-like crystals having an average size of one dimension not greater than 10 nm account for at least 70% of the total number of crystals.
3. The molecular sieve according to claim 1 or 2, wherein: The silicon-aluminum molar ratio of the molecular sieve is 22-45; and / or The total specific surface area of the molecular sieve is not less than 350 m 2 / g, preferably 400-550 m 2 / g; and / or The external specific surface area of the molecular sieve is not less than 120 m 2 / g, preferably 120-230 m 2 / gram.
4. The molecular sieve according to any one of claims 1 to 3, wherein The total pore volume of the molecular sieve is not less than 0.80 cm 3 / g, preferably 0.80-1.50 cm 3 / g; and / or The micropore volume of the molecular sieve is not less than 0.10 cm 3 / g, preferably 0.10-0.20 cm 3 / g; and / or The total acid content of the molecular sieve is not less than 800 μmol / g, preferably 800-1600 μmol / g; and / or The strong acid content of the molecular sieve is not less than 300 μmol / g, preferably 300-600 μmol / g.
5. A method for preparing the nano FER molecular sieve according to any one of claims 1 to 4, characterized in that: The preparation method comprises: (1) crystallizing a raw material mixture formed by a silicon source, an aluminum source, sodium hydroxide, an organic structure directing agent and a solvent; (2) calcining the solid product obtained in step (1); Wherein, the structure of the organic structure directing agent contains a trimethylethylammonium ion structure; In the raw material mixture, the molar ratio of silicon source, aluminum source, sodium hydroxide and organic structure directing agent is 1:a:b:c, wherein a is 0.019-0.045, b is 0.25-0.35 and c is 0.06-0.14; wherein the silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3 and the organic structure directing agent is calculated as trimethylethylammonium ion.
6. The preparation method according to claim 5, wherein: The organic structure directing agent is selected from a quaternary ammonium salt containing a trimethylethylammonium ion structure and / or a quaternary ammonium base containing a trimethylethylammonium ion structure; Preferably, the quaternary ammonium salt containing a trimethylethylammonium ion structure is selected from at least one of trimethylethylammonium chloride, trimethylethylammonium bromide and trimethylethylammonium iodide; and / or The quaternary ammonium base containing a trimethylethylammonium ion structure is selected from trimethylethylammonium hydroxide.
7. The preparation method according to claim 5 or 6, wherein: a is 0.022-0.044; and / or b is 0.26-0.33; and / or c is 0.08-0.14; and / or; The molar ratio of silicon source to solvent is 1:10-50; and / or The solvent comprises water; and / or The silicon source is selected from at least one of silica sol, silica gel and white carbon black, preferably silica sol; and / or The aluminum source comprises sodium aluminate; preferably, the content of Al2O3 in the sodium aluminate is 38-43% by weight, and the content of Na2O is 30-33% by weight; and / or The conditions of the crystallization treatment include: Dynamic crystallization; and / or The crystallization temperature is 40-190°C, preferably 150-180°C; and / or The crystallization time is 1.5-9.0 days, preferably 2.0-8.0 days; and / or The preparation method further comprises: exchanging ammonium and performing heat treatment on the solid material obtained after calcination in step (2).
8. Use of the nano FER molecular sieve according to any one of claims 1 to 4 as an adsorbent or a catalyst for conversion of organic compounds.
9. A catalyst, characterized in that The catalyst contains the nano FER molecular sieve according to any one of claims 1 to 4 and optionally a binder.
10. A method for cracking cumene, characterized in that: The method comprises: contacting cumene with the catalyst according to claim 9 under cracking reaction conditions; Preferably, the cleavage reaction conditions include: The reaction temperature is 280-330°C; and / or The reaction pressure is atmospheric pressure; and / or The weight space velocity of cumene is 3-6h -1 .
Citation Information
Patent Citations
ZSM-35 molecular sieve preparation method
CN109110779A
Method for preparing nano flake FER molecular sieve by hydrothermal synthesis method
CN109650402A
Method for synthesizing FER zeolite nanosheet with controllable thickness by using small molecule template agent
CN115124049A
Cited By
H-type FER molecular sieve as well as preparation method and application thereof
CN122276776A
